بینامتنی پیوند میانِ حکمتِ اسلامی و بلاغتِ فارسی در قرونِ وسطیٰ: Intertextual Connections between Islamic Philosophy and Persian Rhetoric in the Medieval Period (Al-Qamar, 2024)
This study explores the intertextual relationships that developed between Islamic philosophy (ḥikmat-e islāmī) and Persian rhetoric (balāghat-e fārsī) during the medieval period, a time marked by intellectual flourishing and cross-disciplinary exchange across the Islamic world. The research investigates how philosophical concepts—particularly those emerging from Peripatetic, Illuminationist, and later Transcendent traditions—interacted with, shaped, and were transformed by the evolving rhetorical and literary norms of classical Persian prose and poetry. Drawing upon key philosophical texts by thinkers such as Ibn Sina, Suhrawardi, and Mulla Sadra, alongside major Persian literary and rhetorical works, the study demonstrates that Persian rhetoric absorbed metaphysical vocabulary, epistemological frameworks, and symbolic structures directly from philosophical discourse. At the same time, Persian literary practices—metaphor, allegory, semantic nuance, narrative exempla, and poetic imagery—provided philosophy with expressive tools that enriched its argumentative, allegorical, and didactic registers.  The research adopts an intertextual analytical model, tracing shared motifs such as light, intellect, love, motion, and unity across philosophical treatises and Persian literary rhetoric. These motifs reveal a vibrant dialogical space where rational inquiry and aesthetic expression mutually reinforce each other. The study argues that this reciprocal exchange not only reflects the intellectual climate of the medieval period but also played a significant role in shaping the later development of Islamic metaphysics, Persian poetics, and the broader cultural synthesis of the Islamic Golden Age.
Keywords: Intertextuality, Islamic Philosophy, Persian Rhetoric, Medieval Persian Literature, Illuminationism, Metaphysics, Classical Poetics, Intellectual Histor